Ultimate Lateral Load Capacity of Piles in Soils Contaminated with Industrial Wastewater - Mahdi O Karkush; Mahmoud S Abdul Kareem; Mustafa M Jasim (Civil Engineering Journal, 2018)
The present study devoted to determine the ultimate lateral carrying capacity of piles foundation in contaminated clayey soils and subjected to lateral cyclical loading. Two methods have been used to calculate the lateral carrying capacity of piles foundation; the first one is two-line slopes intersection method (TLSI) and the second method is a modified model of soil degradation. The model proposed by Heerama and then developed by Smith has been modified to take into consideration the effects of heavy loads and soil contamination. The ultimate lateral carrying capacity of single pile and piles group (2×2) driven into samples of contaminated clayey soils have been calculated by using the two methods. Clayey soil samples are contaminated with four percentages of industrial wastewater (10, 20, 40 and 100) % of the distilled water used in the soaking process, the soaking procedure of soil samples have been proceeded for 30 days. Also, two ratios of eccentricity to embedded length (e/L = 0.25 and 0.5) have been examined. The results obtained from two analytical methods are well agreed with those obtained experimentally. The ultimate lateral carrying capacity, Pu (analytical) /Pu (experimentally) ranged from (75-8) % and (77-80) % of single pile with e/L = 0.25 and 0.5 respectively. In the piles group the ratio ranged (67-80) % and (71-79) % for e/L = 0.25 and 0.5 respectively.